The Formation of Selenium Nanoparticles Using Ascorbic Acid With the Support of Pomelo-Derived Pectin as a Green Stabilizer - Van Quy Nguyen; Ho Thuy An Nguyen; Bao Thy Vuong; Anh Khoa Ton (Journal of Technical Education Science, 2026)
Selenium nanoparticles (Se NPs) were reported as a source of trace selenium element that is essential for biological activities and nutrition for health. However, their practical applications were hindered by the relatively low stability due to aggregation. In this research, Se NPs were synthesized by chemical reduction using ascorbic acid with the support of the surface capping agent of pectin. The resultant Se NPs possess a hydrodynamic diameter of 140.8 nm (PDI = 0.034) and zeta potential of -15.07 mV through the dynamic light scattering (DLS) method. They showed an absorbance peak at 270 nm, indicating the presence of surface plasmon resonance (SPR) or electronic transitions related to selenium and pectin, and the stability and monodispersed size distribution of the nanoparticles. Besides, SEM-EDX also confirmed the spherical morphology and the existence of selenium in the composition of Se NPs. In conclusion, the creation of Se NPs will open a platform for biomedical, cosmetics, and food supplement research with intensive future investigations by in vitro and in vivo.